کلامِ غالب کی تفہیم کا مسٔلہ - Pitafi, Dr. Shakil (Zoraiz, 2023)
Ghalib is such a unique poet that a huge number of precise and comprehensive interpretations have been written on his verse but the possibilities of understanding and appreciation of his work still exist today. The reason is that he is a multidimensional poet and, in his poetry, there are multiple layers of meanings. That is why he is considered a complex poet and his poetry is categorized ambiguous. In this article, the same issue has been highlighted and it has been tried to clarify that in Ghalib’s poetry there are not only difficulties in his poetic diction but even there are also difficulties in those couplets which seem apparently simple and easy. The reason of this lies in the mysteriousness of his poetry and to overcome this mysteriousness is not easy.